PANCASILA DAN MULTIKULTURALISME INDONESIA - Agustinus Wisnu Dewantara S.S., M.Hum (Studia Philosophica et Theologica, 2015)
Indonesia has founding fathers that have any brilliant ideas. At the time of drawing up the independence, they have debated each other for the sake of strong base of Indonesia. Their ideas have been embraced in conference brochure of BPUPKI. One of the figure that made especial reference in this paper is Soekarno. He have proposed Pancasila, even he embraced Pancasila in one term: “gotong-royong.” The extortion of states of philsosophy of Indonesia is the spirit of “gotong-royong.” Soekarno, in the reality, designed the “gotong-royong” as state of understanding for Indonesia. This paper has a purpose to digging the early idea of the founding of the nation., especially the Soekarno’s idea of Pancasila and “gotong-royong.” Specially, i hope, the discussion of this theme can give any contribution for Indonesian politic and social lives, of which to be felt decline in any ways progressively. Therefore, critical analysis to both of them become the especial pressure. The digging will be focused on Pancasila. Hereinafter, this paper will explain how this research can enrich multiculturalism of Indonesia. The critical contextualization for Indonesian daily live will be searched on last chapter.